2010
DOI: 10.1152/ajpheart.00820.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac oxidative stress is involved in heart failure induced by thiamine deprivation in rats

Abstract: Thiamine is an important cofactor of metabolic enzymes, and its deficiency leads to cardiovascular dysfunction. First, we characterized the metabolic status measuring resting oxygen consumption rate and lactate blood concentration after 35 days of thiamine deficiency (TD). The results pointed to a decrease in resting oxygen consumption and a twofold increase in blood lactate. Confocal microscopy showed that intracellular superoxide (approximately 40%) and H(2)O(2) (2.5 times) contents had been increased. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 30 publications
(28 reference statements)
1
33
1
1
Order By: Relevance
“…It is well known that severe thiamine deficiency is often accompanied by acute congestive heart failure. A recent study showed that thiamine deficiency-induced heart failure in the rat involves oxidative stress induced apoptosis [97]. Furthermore, thiamine deficiency impairs contractile function in cardiomyocytes [98].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that severe thiamine deficiency is often accompanied by acute congestive heart failure. A recent study showed that thiamine deficiency-induced heart failure in the rat involves oxidative stress induced apoptosis [97]. Furthermore, thiamine deficiency impairs contractile function in cardiomyocytes [98].…”
Section: Discussionmentioning
confidence: 99%
“…However, animal experiments have shown that thiamine depletion causes increased reactive oxygen species concentrations and increased cardiomyocyte apoptosis [16,17].…”
Section: Thiamine Deficiency In Heart Failurementioning
confidence: 99%
“…In the way of reducing the activity and expression of HDAC2, oxidative stress may down-regulate the actions of GCs on inflammation, thereby contribute to the inflammatory response and GC resistance. Actually, that may be the cases for cardiovascular diseases and CHF, in which both of increased oxidative stress and chronic inflammation were increasingly recognized as important D r a f t 17 pathogenic mechanisms (Chen et al 2004;Gioda et al 2010;Grieve and Shah 2003;Xu et al 2011). Thus, the simply anti-inflammatory treatment with exogenous glucocorticoids for those patients with CHF always failed to delay the potential heart failure events in the clinic practice.…”
Section: R a F Tmentioning
confidence: 99%